Distillery dry grains (DDG40) in the feeding of suckling calves: evaluating hematological parameters and healthindicators (Research, Society and Development, 2023)
The use of good quality feeds in the calf stage can result in animals with higher weight at weaning and increase the productive efficiency of the production system. In this context, the objective of this work is to evaluate the inclusion of dry distillery grains (DDG) in the feeding of calves from the 8th week until weaning in the 12th week on the sanitary and hematological parameters. Ten animals were used, distributed in a randomized block design according to weight and date of birth in two treatments: control – concentrate with soy bran as a protein source, and DDG – concentrate with DDG40 replacing soybean meal as a protein source. The concentrates were formulated to be isoprotein (20% crude protein), breastfeeding was performed twice a day with whole milk. The experiment lasted 30 days, during which time the evaluation of hematological and health parameters was carried out. The inclusion of DDG in the diet did not change the evaluated parameters until the end of the experiment. A lower consumption of total diet (1.427 x 1.638) and solid diet (0.752 x 0.963) was observed for calves consuming DDG compared to the control diet, but without reflecting on the total weight gain (P>0.05). It is concluded that the inclusion of DDG40 in replacement of soybean meal for calves until weaning can be used without harming the health of the animals.